Cactus Pear Extracts Induce Reactive Oxygen Species Production and Apoptosis in Ovarian Cancer Cells - Feugang, Jean M; Ye, Fei; Zhang, David Y; Yu, Yanhong; Zhong, Mei; Zhang, Sui; Zou, Changping (Nutrition and cancer, 2010)
The protective effect of natural products such as fruits and vegetables against cancer has attracted great attention because of their fewer side effects and therefore, potentially greater safety. We have previously reported that cactus pear mixture aqueous extract (CME) reduces gynecologic cancer cells growth by inducting apoptosis. This study aimed to elucidate the cellular pathway(s) triggered by CME in cancer cells. Normal, immortalized ovarian and ovarian cancer cells (OVCA420, SKOV3) were treated with 5 and 10% CME. After 2 days of treatment, immortalized cells treated with 10% CME accumulated more ROS than untreated cells, whereas cancer cells cultured with 5% and 10% CME exhibited a dramatic increase of reactive oxygen species (ROS). Greater levels of DNA fragmentation, together with a perturbed expression of apoptotic-related (Bax, Bad, caspase 3, Bcl2, p53, and p21) and ROS-sensitive (NF-κB, c-jun/c-fos) genes were observed in the treated cancer cells. After three days of treatment, the NF-κB and p-/SAPK/JNK expressions were decreased, whereas p-AKT was upregulated. The CME significantly induced apoptosis in cancer cells. The results suggest an inhibitory effect of Arizona CME on cancer cell growth through the accumulation of intracellular ROS, which may activate a cascade of reactions leading to the apoptosis.